Philosophical Examination of the Concept of Emotional Intelligence and its Implications for Education - Oyelade, A. F. (NIU Journal of Social Sciences, 2018)
This paper examines the concept of emotional intelligence in the context of education. It examines the concept in the process of education which involves teaching, learning, content and method. The examination is philosophical and it involves logical, linguistic, expository and critical analyses. Thus the research method in this study is philosophical research method. The research method involves the use of philosophical analysis which features logical, linguistic, expository, and critical analyses in the clarification of concepts and issues and their implications for education generally and education in Nigeria specifically. It was found that emotional intelligence involves recognition and management of feelings (moods, drives and so forth) for improved relationships with oneself (intrapersonal) and with others (interpersonal). It was also realised that the concept is laudable and deserves to be promoted in the process of education and in the society generally. However, it was concluded that acquisition of skills implied in the concept, in reality, should concern teachers more than learners since it is the teachers that are at the helm of affairs in the process of education and they (the teachers) determine the tone of the educational society. It was therefore recommended that the concept should lay more emphasis on the teachers and administrators than the learners in the process of education. Keywords: Emotional intelligence, education, philosophical analysis